Aktivitas Menokok Sagu Pada Masyarakat Suku Sentani - Flora F. H. Ohee; Hanro Y. Lekitoo; Christine O.I. Sanggenafa (CENDERAWASIH: Jurnal Antropologi Papua, 2022)
The aim of this research is to attempt to examine the sago chopping activity of the Sentani community in Nolokla Village, East Sentani District, Jayapura Regency, Papua. The method used in this research is descriptive qualitative. The location of this research was conducted in Nolokla Village, East Sentani District, Jayapura Regency. The technique used to determine informants was purposive (intentional) using data collection techniques in the form of in-depth interviews, observation or involved observations and literature studies of literature relevant to the research topic. The results of the research show that the people of Nolokla village have basic knowledge about sago smoking. The activity of sago smoking for the Nolokla community can meet the personal needs of the community. Sago cutting is also done during certain traditional events such as dowry payment and so on. Distribution of processed sago to the Nolokla community to be used as a staple food for Papeda Wraps and Sago Sinole Food.